2012
DOI: 10.1021/tx3002862
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Quantification of 1-Hydroxybutene-2-yl Mercapturic Acid in Human Urine by UPLC- HILIC-MS/MS as a Novel Biomarker for 1,3-Butadiene Exposure

Abstract: 1,3-Butadiene (BD) is a Class 1 carcinogen present at workplaces, in polluted air, in automobile exhaust, and in tobacco smoke. 2-Hydroxybutene-1-yl mercapturic acid (2-MHBMA) is a urinary metabolite often measured as a biomarker for exposure to BD. Here, we show for the first time that an additional MHBMA isomer is present at significant amounts in human urine, 1-hydroxybutene-2-yl mercapturic acid (1-MHBMA). For its quantification, a highly sensitive UPLC-HILIC-MS/MS method was developed and validated. Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 13 publications
(31 reference statements)
1
23
0
Order By: Relevance
“…Moreover, our data confirm recent findings showing significant differences between smokers and non-smokers for AAMA [22], GAMA [34], 2-HPMA [22], 3-HPMA [22], AMCC [22], CEMA [21], SPMA [7], HMPMA [33], and 1-/2-MHBMA [24]. In accordance with the literature, for DHBMA, similar concentrations in smokers and nonsmokers were observed [21,27].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, our data confirm recent findings showing significant differences between smokers and non-smokers for AAMA [22], GAMA [34], 2-HPMA [22], 3-HPMA [22], AMCC [22], CEMA [21], SPMA [7], HMPMA [33], and 1-/2-MHBMA [24]. In accordance with the literature, for DHBMA, similar concentrations in smokers and nonsmokers were observed [21,27].…”
Section: Discussionsupporting
confidence: 93%
“…Although numerous methods for the quantification of different MAs by LC-MS/MS have been reported in the recent past, the majority of those assays target a rather small set of up to six MAs [8,17,[20][21][22][24][25][26]. In addition, many of these methods lack the capability of quantifying MAs from environmental exposures in low levels.…”
Section: Discussionmentioning
confidence: 99%
“…4;6 The availability of sensitive, robust, high throughput methodologies for monitoring human exposure to butadiene (BD) is essential for molecular epidemiology studies of human cancer risk and susceptibility. Although multiple HPLC-ESI − MS/MS methods have been previously described for quantification of BD-mercapturic acids in humans (Table S-1), 2325;2732 many of these methods require at least 0.5 ml of urine, and thus are not applicable to studies where the sample volume is limited (< 0.2 ml). Furthermore, large epidemiological studies typically involve hundreds or even thousands of human subjects, necessitating high throughput analytical strategies.…”
Section: Discussionmentioning
confidence: 99%
“…26 Several mass spectrometry-based methods have been developed for quantification of MHBMA and DHBMA in human urine. 20;2325;2732 However, many of these methods require a large sample volume (> 0.5 ml) and are not amenable to high throughput analysis (Table S-1). …”
Section: Introductionmentioning
confidence: 99%
“…The half life of urinary MAMA is longer than that of urinary MA, suggesting that MAMA is suitable to serve as a biomarker for current MA exposure. Previous studies in styrene (Seutter-Berlage et al, 1978), 1,2-diethylbenzene (Linhart et al, 1996), 1,3-butadiene (Kotapati et al, 2011;Sterz et al, 2012), 1,2,4-trimethylbeneze (Tsujimoto et al, 2000), 2-chloroprene (Eckert et al, 2013), allyl chloride (De Rooij et al, 1996), acrylonitrile (Kedderis et al, 1993), and acrylamide (Sumner et al, 1992) have demonstrated that mercapturic acids are the major detoxification products and the biomarkers of exposure. Our results also reveal that the MA exposure can lead to the formation of MAMA in rat urine, which suggests that MA could be potentially detoxified through GSH conjugation in vivo and excreted through urine.…”
Section: Animal Studymentioning
confidence: 99%